Nexus between entrepreneurial characteristics and small business productivity in Nigeria - Babalola O. Oginni; Samuel O. Omoyele; Isola O. Ayantunji; Folakemi O. Larnre-Babalola; Ramat A. Balogun (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — The productivity challenge confronting small businesses in developing countries has been identified among others to include entrepreneurs’ characteristics. The objective of the study was to investigate the effects of entrepreneurs’ characteristics on the business productivity of SMEs in Nigeria and anchored on the entrepreneur’s innovativeness, experience, orientation, and risk-taking propensity.Method — It was a cross-sectional study carried out among entrepreneurs of SMEs in Southwest Nigeria using a descriptive research survey design. Respondents were selected using a convenience sampling technique. A sample size of 400 respondents was selected for the study, and descriptive statistics such as frequencies and percentages were adopted for data analysis. The hypotheses formulated were tested using chi-square at 0.05 level of significance.Result — The result of the study revealed that an entrepreneur’s characteristics, such as innovativeness, experiences, orientation, and risk-taking propensity, significantly impact productivity. However, innovativeness and risk-taking were paramount among other entrepreneurial characteristics of SMEs in Nigeria.Contribution — The result validated the works of the earlier scholars in the study area and contributed to expanding literature on how entrepreneurs’ characteristics, especially their innovativeness, experience, orientation, and desire to take risks, can solve small business challenges in developing economies.